STRATEGI VISUAL PROMOSI LELANG KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK - Firmansah, Firmansah; Pratikto, Yoga Haryo; Setyawan, Agus Budi (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
The Tanjung Priok Type A Customs and Excise Main Service Office has an annual auction activity agenda. In 2021 the Tanjung Priok Type A Customs and Excise Main Service Office has successfully held 18 auction activities, of these 18 auction activities were able to increase state income by 43 billion rupiah. Realizing the large potential value of state revenue from auction activities, the Tanjung Priok type A main customs and excise service office uses visual content via Instagram social media as a promotional medium for auction activities. By optimizing promotional activities on Instagram social media, it is hoped that it will be able to increase state revenue in auction sector that exceeded previous years. Researchers are interested in dissecting the application of visual strategies contained in the promotion of auction activities in the application of visual elements of illustration, visual elements of color, layout, typography, design processes and the rationale for choosing these strategies, using qualitative methods, with data collection techniques using observation, interviews and documentation, as well as using theories to strengthen analysis. From the results of data analysis, the author obtained the results of choosing a visual strategy and the rationale for choosing this strategy to help promotional activities carried out on Instagram media with the main aim of attracting the audience to be part of the success of the auction activities being held.